The Effect of Health Safety Environment (HSE) on The Productivity of Construction Workers in Wall and Plaster Work at DC MUI BOYOLALI - Arahman, Muhammad Reza; Husodo, Ibnu Toto; Suwandi, Putri Anggi Permata; Purnomo, Didik (Science and Technology Research Centre, Universitas PGRI Semarang, 2024)
Abstract. Analyzing the effect (K3) on the productivity of construction workers in wall and plaster work. The method used in this study is a descriptive method which aims to describe and describe the nature of something that was taking place at the time the research was conducted and to examine the causes of a particular symptom. The results of the analysis and discussion carried out that those who use incomplete K3 equipment do not affect work productivity time. From the results of this case study it can be concluded that the use of incomplete PPE equipment does not affect productivity effectiveness.Keywords: HSE, PPE, Productivity.